2015
DOI: 10.1158/0008-5472.can-14-2173
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Links between E2F Control and Mitochondrial Function

Abstract: The family of E2F transcription factors is the key downstream target of the Retinoblastoma tumor suppressor protein (pRB), which is frequently inactivated in human cancer. E2F is best known for its role in cell cycle regulation and triggering apoptosis. However, E2F binds to thousands of genes and, thus, could directly influence a number of biological processes. Given the plethora of potential E2F targets, the major challenge in the field is to identify specific processes in which E2F plays a functional role a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…Additionally, at a cellular and organismal level CDK4/6 activity plays important roles in controlling gluconeogenesis and responsiveness to insulin (Lopez-Mejia and Fajas, 2015). RB has been shown to bind to mitochondria and regulate apoptotic functions(Hilgendorf et al, 2013), while E2F has been shown to drive mitochondrial-dependent apoptosis in Drosophila(Ambrus et al, 2013; Benevolenskaya and Frolov, 2015). Interestingly, in fibroblastic models RB loss is associated with increased glutamine utilization (Clem and Chesney, 2012; Reynolds et al, 2014), and loss of RBF has been associated with altered glutamine catabolism in drosophila (Nicolay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at a cellular and organismal level CDK4/6 activity plays important roles in controlling gluconeogenesis and responsiveness to insulin (Lopez-Mejia and Fajas, 2015). RB has been shown to bind to mitochondria and regulate apoptotic functions(Hilgendorf et al, 2013), while E2F has been shown to drive mitochondrial-dependent apoptosis in Drosophila(Ambrus et al, 2013; Benevolenskaya and Frolov, 2015). Interestingly, in fibroblastic models RB loss is associated with increased glutamine utilization (Clem and Chesney, 2012; Reynolds et al, 2014), and loss of RBF has been associated with altered glutamine catabolism in drosophila (Nicolay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in mitochondrial biogenesis have also been implicated in the ineffective erythropoiesis observed in RB1 mutant mice (Sankaran et al 2008), and other studies have shown that autophagy inhibitors also promote a healthy mitochondrial network in RB1 mutant cells and promote differentiation Zacksenhaus 2010, 2011). Taken together, these studies suggest that metabolic changes are likely a major cause of the differentiation defects seen in RB1 mutant mouse tissues (for review, see Benevolenskaya and Frolov 2015).…”
Section: The Cellular Consequences Of Rb Inactivationmentioning
confidence: 88%
“…Intriguingly, the responsible mechanism may include changes in catalytic activity of histone-modifying enzymes, like the KDM5 family. In addition to pRB, other RB family members, upstream regulators of pRB, and E2F family proteins may directly regulate metabolism in order to maintain cellular homeostasis or drive cell proliferation, differentiation, and survival (Macleod 2008;Benevolenskaya and Frolov 2015). In particular, E2f1 orchestrates not only a proliferative response but also a metabolic response in conditions requiring adaptations to new energy demands (e.g., fasting and cold) (Blanchet et al 2012).…”
Section: Discussionmentioning
confidence: 99%